2016
DOI: 10.1002/mats.201600033
|View full text |Cite
|
Sign up to set email alerts
|

Radius of Gyration, Mean Span, and Geometric Shrinking Factors of Bridged Polycyclic Ring Polymers

Abstract: This study concerns the equilibrium geometric properties of a family of cyclic chains, referred to as the “bridged polycyclic rings,” which have f flexible subchains bridging two common branch points. By increasing the number of bridges, f, this family encompasses the usual linear chain (f = 1), monocyclic ring (f = 2), bicyclic θ‐shaped polymer (f = 3), and multicyclic rings with increasing topological complexity. Results of their radius of gyration, mean span, and, consequently, geometric shrinking factors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 93 publications
(293 reference statements)
4
5
0
Order By: Relevance
“…2 (a) the universal values of the ratio X/2R g in the θ-solvent limit for linear and ring polymers are found to be 1.139 ± 0.005 and 1.250 ± 0.005, respectively. These values are in close agreement with previously reported values of 1.132 and 1.13 for linear chains and 1.253 for rings obtained from BD simulations [71] and analytical theory based on the Gaussian chain model [84]. The universal value of the ratio X R /X L under θ-solvent conditions is found to be 0.780 ± 0.005, which is also in good agreement with the predicted value of 0.796 obtained from the Gaussian chain model [84].…”
Section: Universal Static Propertiessupporting
confidence: 93%
“…2 (a) the universal values of the ratio X/2R g in the θ-solvent limit for linear and ring polymers are found to be 1.139 ± 0.005 and 1.250 ± 0.005, respectively. These values are in close agreement with previously reported values of 1.132 and 1.13 for linear chains and 1.253 for rings obtained from BD simulations [71] and analytical theory based on the Gaussian chain model [84]. The universal value of the ratio X R /X L under θ-solvent conditions is found to be 0.780 ± 0.005, which is also in good agreement with the predicted value of 0.796 obtained from the Gaussian chain model [84].…”
Section: Universal Static Propertiessupporting
confidence: 93%
“…Extensive study on chemically unfolded proteins found a R 0 value equal to 1.33 28 , whereas the fit of our experimental data gave a R 0 value equal to 0.22, thus divided by six. Such a result can be interpreted by the presence of an average of 6-7 bridges within the polymer 29 , which is coherent considering the PBLG polymer in a coil disordered state, internally connected . e Infrared spectra of CO coordinated at the nanoparticle surface and of peptide bond of the polymer within the assemblies (at 0 eq., 0.05 eq., 0.5 eq., and 1 eq.).…”
Section: Resultsmentioning
confidence: 67%
“…The difference in the chain size between the linear and the ring polymer topology is conventionally expressed by the shrinking factor. [ 53 ] This geometric factor is most often defined as the ratio of the mean square of the radii of gyration G = ( R g 2 ) r /( R g 2 ) l of the ring and linear chains. For ideal Gaussian chains, G = 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, one should note that the span‐based shrinking factors show higher values than those based on the radius of gyration. [ 53 ]…”
Section: Resultsmentioning
confidence: 99%